Evaluation Roots: An International Perspective - Carden, Fred; Alkin, Marvin C. (Journal of MultiDisciplinary Evaluation, 2012)
<!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 9]> Normal 0 false false false EN-US JA X-NONE <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]--> Background: The second edition of Evaluation Roots has expanded to more global coverage, but no chapter emerged on development theory in low and middle income countries (LMICs). Purpose: The purpose of this article is initiate a conversation on filling this gap. Setting: Not applicable. Intervention: Not applicable. Research Design: Not applicable. Data Collection and Analysis: Desk review. Findings: Two important distinctions emerged in evaluation roots in LMICs. The first is that much evaluation fits effectively on the Theory Tree as it is presented, with perhaps some nuance, but we see a collective rather than individual origin of the evaluation theory writings we have uncovered. The second is the nature of the formal evaluation work in LMICs; its practical origins are not yet formalized into full prescriptive theory. The paper notes the prominence of external actors (such as the donor community) in formalizing evaluation practice, while at the same time observes important threads are developing in different regions of the world. This paper proposes a way to thinking about evaluation in LMICs that is based on practice. The paper suggests a need for evaluation analysts, especially those in LMICs, to build a more comprehensive knowledge and documentation on development evaluation and, more broadly on building the field of evaluation in LMICs.